Destructive effects of transitional metal ions on interfacial film of carbon anode for lithium-ion batteries. (10th June 2022) - Zhang, Jingjing; Li, Wenbo; Wang, Jie; Wang, Peng; Sun, Jinlong; Wu, Shumin; Dong, Hong; Ding, Hao; Zhao, Dongni; Li, Shiyou
Abstract: The dissolution, migration, and deposition of transition metal (TM) ions are the main reasons for the capacity degradation of lithium-ion batteries, which significantly affect their comprehensive electrochemical performance and safety. In this work, the effects of different TM ions (Mn 2+, Co 2+, and Ni 2+ ) on the electrochemical performance of lithium/mesocarbon microbeads half-cell were compared, and the mechanism was discussed. It is found that Mn 2+ ions inhibit the decomposition of lithium salt and promote the decomposition of solvents, resulting in the crack of electrode material and solid electrolyte interface (SEI) film and the increase of capacity degradation. In contrast, Ni 2+ ions promote the decomposition of lithium salts to a certain extent, thus inhibiting the excessive damage to the SEI film and electrode material. This study can provide theoretical support and research direction for the design of the electrolytes that can alleviate the damage of TM ions to the anode and the SEI film. Graphical abstract: Image, graphical abstract